Sensitisation to airborne allergens as a risk factor for allergic rhinitis and asthma in the Polish population - Lipiec, Agnieszka (Postepy Dermatol Alergol, 2019)
INTRODUCTION: The patterns of sensitisation to airborne allergens and their association with allergic diseases have been analysed in different geographical regions. AIM: To analyse the impact of sensitisation to airborne allergens on allergic rhinitis (AR) and asthma in different age groups of the Polish population. MATERIAL AND METHODS: Completed questionnaires of 18,617 subjects (53.8% females), collected within the ECAP, a cross-sectional multicentre study, were analysed. Three groups of respondents were included: 6–7-year-olds (24.2%), 13–14-year-olds (25.4%), 20–44-year-olds (50.4%). The clinical part (an anamnesis, physical examination, spirometry, skin prick tests and an assay of major airborne allergen-specific IgE) was attended by 25.7% of the respondents. RESULTS: The AR was most strongly related to sensitisation to Dermatophagoides pteronyssinus, with the highest odds ratios of 10 in two younger groups and of 16 for persistent AR in children. It was also the most important risk factor for allergic asthma, with odd ratios from 8.34 in children to 6.40 in adolescents. Sensitisation to grass pollen allergens was a major risk factor for both AR, with odds ratios from 9.16 in adults to 7.87 in adolescents, and asthma, with odds ratios from 6.16 in adolescents to 5.67 in adults. CONCLUSIONS: AR and asthma shared common risk factors, independently of age. Sensitisation to airborne allergens was significantly associated with asthma and, even more strongly, with AR, across all age groups. The AR was the strongest risk factor for allergic asthma in the youngest group. Persistent AR increased asthma risk more than intermittent AR in all age groups.